Elementary quantum mechanics - Saxon, David S. (Dover Publications, Inc., 2012)
"Based on lectures for an undergraduate UCLA course in quantum mechanics, this volume focuses on the formulas of quantum mechanics rather than applications. Topics include the dual nature of matter and radiation, state functions, linear momentum, the motion of a free particle, Schro?dinger's equation, approximation methods, angular momentum, and many other subjects. 1968 edition"-- Provided by publisher.